Vendor and pedestrian experiences of their ‘right to the city’ in street design and management in small urban centres in the Vhembe District, South Africa - Wendy Tsoriyo; Emaculate Ingwani; James Chakwizira; Peter Bikam (Town and Regional Planning, 2021)
The demand for a spatial turn to enhance citizens’ ‘right to the city’ is gaining more momentum in this era than previously. This is particularly evident within the South African urban space context. This article examines the vendor and pedestrian (street users) experiences of their ‘right to the city’ in street design and management in small urban centres in the Vhembe District of South Africa. The article adopted a case-study survey design and a mixed methods research approach. Data was collected by means of both key informant interviews with eight key experts in street design and management and a street intercept questionnaire survey administered to a total of 100 vendors and 400 pedestrians in the selected case study towns. Data analysis was done quantitatively through average users’ satisfaction scores with a spatial quality and qualitatively through thematic analysis. Lefèbvre’s ‘right to the city’ theory was used to extract meaning from the research findings. The findings reveal that street users in all the towns of the study are dissatisfied with the spatial quality of safety, while accessibility was a challenge particularly in Thohoyandou Town. The findings reveal that economic, historical, and geographical differences affect street users’ ‘right to the city’ experiences. Questions such as “Whose ‘right to the city’?” and “Which ‘right to the city’?” remain paradoxical. To create more spatially just streets, where vendors and pedestrians can enjoy their disparate ‘right to the city’ claims, users need to embrace the right to differences and municipalities in small urban centres need to continue to learn, experiment, and co-create urban space with the vendors and the pedestrians.